Intratympanic gentamicin compared with placebo for Ménière's disease - Fernanda de Amesti; Maria Jesus Santander; Matias Winter (Medwave, 2022)
INTRODUCTION Ménière's disease is a multifactorial disorder affecting the inner ear, characterized by episodes of spontaneous and recurrent vertigo, fluctuating hearing loss and tinnitus. Intratympanic gentamicin therapy has been used to reduce the intensity and frequency of attacks in intractable Ménière's disease, but it is associated with hearing loss. There is controversy regarding its efficacy and safety.